2017
DOI: 10.1007/s00709-017-1135-7
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic microorganisms in Puto superbus (Leonardi, 1907) (Insecta, Hemiptera, Coccomorpha: Putoidae)

Abstract: The scale insect Puto superbus (Putoidae) lives in mutualistic symbiotic association with bacteria. Molecular phylogenetic analyses have revealed that symbionts of P. superbus belong to the gammaproteobacterial genus Sodalis. In the adult females, symbionts occur both in the bacteriocytes constituting compact bacteriomes and in individual bacteriocytes, which are dispersed among ovarioles. The bacteriocytes also house a few small, rod-shaped Wolbachia bacteria in addition to the numerous large, elongated Sodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 78 publications
(126 reference statements)
0
21
0
Order By: Relevance
“…It should be underlined that this is the first report on the occurrence of a Sodalis -like symbiont in Fulgoromorpha. So far, the presence of Sodalis -allied bacteria has been reported in several insect groups which feed on different food such as follows: leafhoppers (Koga et al 2013 ; Michalik et al 2014 ), scale insects (von Dohlen et al 2001 ; Husnik and McCutcheon 2016 ; Szklarzewicz et al 2018 ), tsetse flies (Dale and Mauldin 1999 ), Hippoboscidae flies (Dale and Maudlin 1999 ; Nováková and Hypša 2007 ; Chrudimský et al 2012 ), Philopteridae lice (Fukatsu et al 2007 ), weevils (Toju and Fukatsu 2011 ), and some stinkbugs (Kaiwa et al 2010 ). The relationships between insects and Sodalis -like bacteria are usually considered relatively recent due to the fact that they possess relatively large genomes, which are larger than the genomes of long-established symbionts and are comparable to the genome size of free-living bacteria (Husnik and McCutcheon 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It should be underlined that this is the first report on the occurrence of a Sodalis -like symbiont in Fulgoromorpha. So far, the presence of Sodalis -allied bacteria has been reported in several insect groups which feed on different food such as follows: leafhoppers (Koga et al 2013 ; Michalik et al 2014 ), scale insects (von Dohlen et al 2001 ; Husnik and McCutcheon 2016 ; Szklarzewicz et al 2018 ), tsetse flies (Dale and Mauldin 1999 ), Hippoboscidae flies (Dale and Maudlin 1999 ; Nováková and Hypša 2007 ; Chrudimský et al 2012 ), Philopteridae lice (Fukatsu et al 2007 ), weevils (Toju and Fukatsu 2011 ), and some stinkbugs (Kaiwa et al 2010 ). The relationships between insects and Sodalis -like bacteria are usually considered relatively recent due to the fact that they possess relatively large genomes, which are larger than the genomes of long-established symbionts and are comparable to the genome size of free-living bacteria (Husnik and McCutcheon 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…To replicate Sodalis evolution in different environments, the MOEA was applied to i RH830 that was supplied with a tsetse-specific blood medium, a famine medium and a medium that mimics plant sap (, scenario i). Sap was chosen as a comparison medium as Sodalis -allied symbionts have been identified in a range of phytophagic insects [86–91]. The algorithm underwent ten runs of 3000 generations and the resulting solutions were collated.…”
Section: Resultsmentioning
confidence: 99%
“…The only difference concerns the last step of transport -in G. brachypodii, symbionts gather in the perivitelline space where they create a characteristic 'symbiont ball', whereas the symbionts of A. aceris and G. spuria initially create a short-term 'cup-like accumulation' in the perivitelline space, then they disperse and migrate to the oocyte cytoplasm . It should be noted that besides the eriococcid species which have been examined so far, infection at the anterior pole of the oocyte has been observed in pseudococcids (von Dohlen et al, 2001) and putoids (Szklarzewicz et al, 2018). In auchenorrhynchans, aphids, whiteflies, psyllids and most species of scale insects symbionts migrate to the oocyte through the follicular epithelium surrounding the posterior pole of the oocyte (reviewed in Buchner, 1965;Szklarzewicz and Michalik, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These insects usually possess one type of obligate symbiont (also termed the primary symbiont, such as Buchnera aphidicola in aphids, Carsonella ruddii in psyllids, or Portiera aleyrodidarum in whiteflies), which may coexist with facultative (secondary) symbionts and all symbionts are transmitted vertically to the offspring (reviewed in Baumann, ). In contrast to other sternorrhynchans, scale insects are characterized by: (i) a much higher diversity of symbiotic microorganisms; (ii) different distribution of symbionts in the host insect body and (iii) different modes of symbiont transmission from one generation to the next (Fukatsu and Nikoh, ; von Dohlen et al ., ; Thao et al ., ; Gruwell et al ., ; Szklarzewicz et al ., ; Niżnik and Szklarzewicz, ; Matsuura et al ., ; Ramirez‐Puebla et al ., ; McCutcheon and von Dohlen, ; Vashishtha et al ., ; Dhami et al ., ; Rosenblueth et al ., ; Koga et al ., ; Rosas‐Pérez et al ., ; Husnik and McCutcheon, ; Michalik et al ., ; Szabo et al ., ). Previous investigations have shown that scale insects may serve as hosts for various microorganisms (bacteria and/or yeast‐like symbionts), e.g., representatives of the family Diaspididae harbour the Bacteroidetes bacterium Uzinura diaspidicola (Gruwell et al ., ), and some eriococcids possess betaproteobacterial Burkholderia symbionts (Michalik et al ., ), whereas scale insects belonging to Pseudococcidae: Pseudococcinae are associated with the betaproteobacterium Tremblaya princeps and various species of gammaproteobacteria (von Dohlen et al ., ; Thao et al ., ; McCutcheon and von Dohlen, ; Husnik and McCutcheon, ; Szabo et al ., ).…”
Section: Introductionmentioning
confidence: 99%